Lime peel extract induced NiFe2O4 NPs: Synthesis to applications and oxidative stress mechanism for anticancer, antibiotic activity - Malik Abdul Raouf; Aziz Muhammad Hammad; Atif Muhammad; Irshad Muhammad Sultan; Ullah Hafeez; Nguyen Gia Tuan; Ahmed Hijaz; Ahmad Shafiq; Botmart Thongchai (Elsevier, 2022)
Nanobiotechnology, joined with green science, has incredible potential for the advancement of novel and important products that benefit human health, climate, and industries. Green chemistry of materials from synthesis to diverse biomedical applications is a talk of town in today's sustainable ideal world. Green synthesized nickel ferrites nanoparticles via biogenic lime peel extract (LPE) are investigated with precision and complete trail has been reported as multiple efficacies. The fcc crystal structure with the crystallite size (31 nm) were accessed by the XRD, magnetic properties using VSM, and FTIR for the functional group analysis of NiFe2O4 nanoparticles mediated by Lime peel extract (NiFe2O4@LPE NPs). From TEM and SEM analysis the average diameter of the NPs was observed in the range of 31-35 nm. In 3D view, the surface morphology was analyzed by the AFM. NiFe2O4@LPE NPs were used to assess cytotoxicity and cellular morphological alterations in In Vitro cervical cancerous cells (HeLa). Nanosized NiFe2O4@LPE accompanied the considerable NPs topology induced dose dependent MMP in HeLa cells unlike the previous interpretation of controlled metabolism anticancer activity for HeLa cancerous cells. Therefore, it is referred by oxidative stress and reduction phenomena for anticancer effects and inactivation of carcinogen. Moreover, Antioxidant DPPH radical scavenging method and antibacterial Bacillus subtilis, Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus activity were observed in the synthesized nickel ferrites NPs. (c) 2022 The Author(s). Published by Elsevier B.V. on behalf of King Saud University. This is an open access article under the CC BY license (http://creativecommons.org/licenses/by/4.0/).